THE BENEFIT OF COMPETENCE IN DEVELOPING THE NATION - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Good employee competence is needed in order to establish a good service. The higher the competence of the employee, the higher the performance of the organization and vice versa. Employee competence is very important due to organizational performance improvement. In a private sector, qualified employees will improve the quality of the customer service, so that, an organization seems to always continue improving the quality of its customer service and provides a decent life for its customers (Abomaleh and Zahari, 2014). According to Spencer in Sutoto (2004), he defined competence as the underlying characteristic of an individual that is causally related to criterion referenced effective and or superior performance in a job situation. The concept of competence as the combination of skills, knowledge, behavior, experience and feeling of being in on things that Jubek state employees uses in carrying out their work and they are cited to achieving result.